Elastisitas Kemiskinan terhadap Pertumbuhan Pengeluaran per Kapita di Jawa Barat 2017-2024 - Muttaqin, Zenal; Aos, Aos (Syntax Literate, 2025)
This study aims to analyze the elasticity of poverty to per capita expenditure growth in West Java over the period 2017-2024. Using secondary data on the percentage of poverty and average per capita expenditure, this study applies the elasticity calculation method to measure the responsiveness of changes in the poverty rate to changes in per capita expenditure. The results show that the relationship between per capita expenditure and poverty varies from year to year, with some periods showing high responsiveness. These findings provide important implications for the formulation of poverty alleviation policies in West Java.